Cardiovascular Risk Profile and Prevalence of Microalbuminuria in Patients With Type 2 Diabetes Mellitus: The Campaign Disease Registry Results - Ebrahim M. A (Journal of Rawalpindi Medical College, 2017)
To assess the cardiovascular risk profile of patients with type 2 diabetes mellitus (T2DM), the prevalence of microalbuminuria, and the prescription pattern in management of overall cardiovascular/renal risk in out patient practice. Methods: In this cross sectional study consecutive adult patients with T2DM signed the informed consent and were interviewed by the investigator to establish the cardiovascular risk profile. Presence of microalbuminuria (20–200mg/l) was diagnosed using Micral-Test® strips. Analysis was done by descriptive statistics, and multivariate logistic regression was performed to identify the independent risk-factors for the development of microalbuminuria. Results: Of the 1763 patients enrolled, data was analyzed on 1596 patients. Major cardiovascular riskfactors included hypertension (55.4%), sedentary lifestyle (49.8%), and metabolic syndrome (30.5%). Microalbuminuria was prevalent in 55.6% (95% CI 53.1-58.0) patients. On multivariate analysis, significant association was observed with total cholesterol (p = 0.029, OR: 2.26, 95% CI: 1.09 – 4.71) and diastolic BP (p = 0.015, OR: 2.67, 95% CI: 1.21 – 5.91). The most commonly prescribed antihypertensive drugs were angiotensin-converting enzyme inhibitors (41.7%), calcium channel blockers (13.2%) and beta blockers (10%), while most commonly prescribed antidiabetic drugs were sulfonylureas (61.9%), biguanides (56.1%) and thiazolidinediones (17.4%). Conclusions: Patients with T2DM are at increased cardiovascular risk specifically with uncontrolled diastolic blood pressure and high total cholesterol levels. There is also a high prevalence of microalbuminuria in patient with T2DM.